Role of food nutrients and supplementation in fighting against viral infections and boosting immunity: A review - Thirumdas, Rohit; Kothakota, Anjinelyulu; Pandiselvam, R.; Bahrami, Akbar; Barba, Francisco J. (Trends in food science & technology, 2021)
The viral infections can be highly contagious and easily transmissible, which even can lead to a pandemic, like the recent COVID-19 outbreak, causing massive deaths worldwide. While, still the best practical way to prevent the transmission of viruses is to practice self-sanitation and follow social distancing principles, enhancing the individual's immunity through the consumption of proper foods containing balanced nutrients can have significant result against viral infections. Foods containing nutrients such as vitamins, minerals, fatty acids, few polysaccharides, and some non-nutrients (i.e. polyphenols) have shown therapeutic potential against the function of viruses and can increase the immunity of people. The results of conducted works aiming for studying the potential antiviral characteristics of diverse groups of foods and food's nutrients (in terms of polysaccharides, proteins, lipids, vitamins, and minerals) are critically discussed. Nutrients, besides playing an important role in maintaining normal physiology of human's body and healthiness, are also required for enhancing the immunity of the body and can be effective against viral infections. They can present antiviral capacity either by entering into the defensive mechanism directly through interfering with the target viruses, or indirectly through activating the cells associated with the adaptive immune system. During the current situation of COVID-19 pandemic (the lack of proper curative viral drug), enhancing the immunity of individual's body through proposing the appropriate diet (rich in both macro and micro-nutrients) is one of few practical preventive measures available in fighting against Coronaviruses, this significant health-threatening virus, as well as other viruses in general. [Display omitted] •Nutrients can induce several signaling pathways regulating the immune system.•Nutrients modulate macrophages’ function against infections as anti-inflammatory.•Lipids and their bioactive metabolites are highly effective against HIV and HCV.•Minerals regulate immune cells’ (macrophages, neutrophils, T and B cells).•Antiviral drugs + nutrient supplements could obtain promising results.